Faktor-Faktor Yang Mempengaruhi Status Gizi Balita: Systematic Review - Jasmawati Jasmawati; Rizky Setiadi (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
Nutrition problems are inseparable from food problems because nutritional problems arise as a result of deficiency or excess nutrient content in food. Fulfillment of nutrition in children under five is a factor that must be considered, because the vulnerable development period of nutrition is in infancy. A serious malnutrition can cause death in children. Thus, it is very important to do a weighing toddler regularly every month so that growth can be followed. Therefore it is necessary to have research that describes the literature review regarding the factors that influence the nutritional status of children under five. Research purposes is finding out what factors can affect the nutritional status of children under five based on the results of the literature review. The research used in this research is literature research or literature study. The results of the synthesis of the research article show that there is an influence between the factor of mother's education, mother's knowledge about toddler nutrition, and the history of exclusive breastfeeding to the nutritional status of toddlers. There is an influence between the factors of mother's education level, mother's knowledge about toddler nutrition, and the history of exclusive breastfeeding on the nutritional status of children under five based on the literature review Keywords : Education, Knowledge, Exclusive Breastfeeding, Nutritional Status Of Children Abstrak Masalah gizi tidak terlepas dari masalah makanan karena masalah gizi timbul sebagai akibat kekurangan atau kelebihan kandungan zat gizi dalam makanan. Pemenuhan gizi pada anak balita merupakan faktor yang harus diperhatikan, karena periode perkembangan yang rentan gizi adalah pada masa balita. Kekurangan gizi yang serius dapat menyebabkan kematian pada anak. Dengan demikian, sangat penting dilakukannya penimbangan berat badan balita secara teratur setiap bulan agar dapat diikuti pertumbuhannya. Oleh karena itu perlu adanya penelitian yang mendeskripsikan literature review mengenai faktor-faktor yang mempengaruhi status gizi balita. Tujuan penelitian untuk mengetahui faktor – faktor apa saja yang dapat mempengaruhi status gizi balita berdasarkan hasil literature review. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan atau kajian literatur. Hasil sintesis artikel penelitian menunjukkan bahwa adanya pengaruh antara faktor pendidikan ibu, pengetahuan ibu tentang gizi balita, dan riwayat pemberian ASI Eksklusif terhadap status gizi balita. Terdapat pengaruh antara faktor tingkat pendidikan ibu, pengetahuan ibu tentang gizi balita, dan riwayat pemberian ASI Eksklusif terhadap status gizi balita berdasarkan hasil literature review. Kata Kunci: Pendidikan, Pengetahuan, ASI Eksklusif, Status Gizi Balita